A Spanish Sentence Repetition Task and its relationship with spontaneous language in children aged 30 to 36 months - Bravo, Natalia; Mariscal, Sonia; Casla, Marta; Lázaro, Miguel (Frontiers in Communication, 2024)
Sentence Repetition Tasks (SRTs) have been convincingly established as a reliable tool for assessing child language development. However, there are important aspects of this task that deserve more attention. For example, few studies have explored their potential role for identifying language disorders in children under 4 years of age, as almost all evidence refers to children above this age. There is also scarce evidence regarding the relationship between the results of these tasks and measures of spontaneous language. To address this gap, we conducted a study with 24 Typically Developing (TD) monolingual Spanish speakers aged between 30 and 36 months. They performed a Spanish Sentence Repetition Task (SSRT), and their language was recorded and analyzed during spontaneous play with their parents. Variables such as Mean Length of Utterance (MLU), an index of lexical diversity (ILD) and the structure of the Noun Phrase were considered.The statistical analyses reflect a positive and significant correlation between the results obtained in the SSRT and both the MLU and Noun Phrase structure. A positive and significant relationship is also obtained between the MLU in repetition and the MLU of spontaneous language. However, no significant correlation is found between the ILD with either the SSRT or the other measures of spontaneous language. Based on these results, we interpret that the SSRT effectively mirrors the language development of children measured through spontaneous production and is suitable for assessing language skills of Spanish children under 4 years old.